THE STUDY OF ORGANIZATIONAL PERFORMANCE IN SMALL SCALE MANUFACTURING INDUSTRIES IN SRI LANKA - Pushpanathan, A. (Knowledge Hub, 2008)
This study investigates the organizational performance of small scale manufacturing industries in Sri Lanka. The main objective of the study is to analysis the performance of family and non-family controlled firm. Family and non-family controlled firm were considered as independent variables, and organizational performance - profitability, employee turnover, and employee morale- was considered as dependent variable. This study utilized data from 220 small scale manufacturing industries those who are registered under the Chamber of Commerce in Sri Lanka. For the purpose of evaluating hypotheses, the questionnaire data were entered in the SPSS 11.0 package for measuring the factor Analysis. Factor analysis is used to reduce variables and test reliability and validity of scales. Then the regression results of independent and dependent variables were measured in this study. The results indicated that family controlled firm has more significant effect on profitability and employee turnover than that of non-family controlled firm. But the insignificant effect observed between family and non-family controlled firm and employee morale.
Keywords: Family controlled Firm; Non-family Controlled Firm; Profitability; Employee Morale; Employee Turnover